Nursing Hourly Rounds Increase Patient Satisfaction : Literature Review - Cencen Hendra Setiawan; Ati Surya Mediawati (Media Keperawatan Indonesia, 2023)
The quality of hospital services depends on the quality of nursing care provided to patients, Nurses are a large fleet in hospitals both in terms of number and hours of service because nurses are 24 hours with patients. Patient satisfaction is an indicator of the quality of care that has been provided to patients, which until now has become the focus of attention for every health service to further enhance the role and function of nurses in improving the quality of care. The aim is to identify the effect of the implementation of Nursing Rounds on patient satisfaction—systematic review using electronic databases identified from Pubmed, EBSCOhost and Google Scholar. Search using keywords, namely nurse, Nursing rounds, hourly rounds and patient satisfaction. The search results contained seven articles that were filtered from 2017-2021 which showed that Nursing rounds could increase patient satisfaction, improve patient safety, and prevent extravasation of infusion fluids. Nursing rounds can also be done together with other professions. Nursing Rounds activities carried out by nurses in a measured and planned manner can increase patient satisfaction. Patient satisfaction is greatly influenced by the role of nurses in carrying out nursing rounds for patients.